A unilateral, left-sided aberrant origin of the long thoracic nerve - John F. Mills; Aditya Srinivasan; Neil Gildener-Leapman; Amanda S. Khan; Natalia Lowry; Jeffrey Fahl; Michael P. Smith (Elsevier, 2023)
Background: Variations in the roots of the brachial plexus and their branches may cause unexpected complications during surgical procedures of the neck. In this report, we show an extremely rare variation of the long thoracic nerve. Methods: During routine dissection of the posterior triangle of the neck in a white female cadaver, a variation in a branch of the brachial plexus was observed and documented. Further dissection of the axilla and anterolateral thoracic wall were performed to follow the course of the anomalous superficial nerve. Results: The abnormal nerve was discovered to be a variation of the long thoracic nerve (LTN) formed from a supraclavicular union of only the C6 and C7 spinal nerve roots. Conclusions: Variations in the anatomy of the brachial plexus are not uncommon, but variations of the LTN are rare. Awareness of the LTN in relation to the brachial plexus is useful for the head and neck surgeon operating in less often encountered spaces to prevent injury.